Kesiapan Lapas Kelas I Bandar Lampung Dalam Menghadapi Bencana Alam - Ganda Aulia Wicaksana; Padmono Wibowo (Universitas Batanghari Jambi, 2021)
The condition of correctional institutions in Indonesia which is currently over capacity or overcapacity as well as the geographical location of Indonesia which is surrounded by dozens of active volcanoes which are also in the zone or ring of fire area which makes the condition of the Indonesian state very dangerous and prone to disasters. However, there are still many lack of employee awareness regarding work accidents and a lack of Occupational Safety and Health signs in the correctional Technical Implementation Unit. So that it caused a lot of riots in the correctional institutions because of the disaster. The purpose of this study discusses the factors that cause accidents in prisons, the implementation of evacuation routes in prisons and a review of the implementation of evacuation routes in prisons. The method used in this research is descriptive method with a qualitative approach, the data sources obtained are field observations, interviews and literature studies. Data collection techniques are direct observation and interviews as primary data and literature studies and theory studies as secondary data. This research was conducted at the Class I Correctional Institution in Bandar Lampung. The results of this study are to be able to find out the factors that cause accidents in prisons, to find out the implementation of evacuation routes in prisons and to be able to evaluate the implementation of safety for natural disasters and other disasters based on the results of implementing the evacuation routes in prisons and the mechanisms for implementing evacuation routes. as the readiness of a correctional institution in dealing with, anticipating and preventing disasters. This study discusses the importance of fulfilling occupational safety and health signs in the form of evacuation routes to provide a sense of security and safety at work. This research also discusses the implementation of occupational safety and health signs as the fulfillment of the rights of prisoners. So that this research is expected to make people's views about prisoners not always negative and change people's views on the life of prisoners in prisons.